Pengaruh Laba Bersih, Komponen Arus Kas, Ukuran Perusahaan terhadap Harga Saham Perusahaan Perbankan pada Masa Pandemi Covid-19 - Sindy Patika Sari; Hendra Sanjaya Kusno; Ramli Ramli (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study aims to determine the effect of Net Profit, Cash Flow Components, and Firm Size on stock price of banking companies during the Pandemic Covid-19 (Case Study at conventional banks listed on the Indonesia Stock Exchange for 2020-2021). The data used in this study is panel data sourced from financial statements published by the Indonesia Stock Exchange (IDX) during the 2020-2021 period. The population in this study was a conventional bank for the 2020-2021 period, with the sampling method was purposive sampling so that the number of samples was 29 banks. The analysis method used is multiple linear regression analysis. Data management uses the IBM SPSS Statistics program 25. The results of this study indicate that Net Profit, Operating Cash Flow, Investment Cash Flow, Funding Cash Flow, and Firm Size simultaneously effect on stock prices; Net Profit partially has a positive and significant effect on stock prices; Operating cash flow, Investment Cash Flow, Funding Cash Flow and Firm Size partially have no effect on stock prices.